Uso de piquiá (Caryocar villosum) como fonte de produtos biotecnológicos - Souza, Erica da Silva (Brasil, 2023)
The National and International market has used Amazonian fruits due to research that indicates the biological properties present in their extracts. Among the Amazonian fruits, there is the piquiá (Caryocar villosum). This work’s objective was to use bark, pulp, and seed piquiá fruit to handmape soap roduction. Maceration was the method used to prepare the glycolic extract and the formulation of the soap. There were seven physicalchemical tests of soap quality. It was possible to observe a good consistency and resistance of the products. The results showed that the piquiá fruit could used such a cosmetic product and encourage future studies for more specific analyses.